2019
DOI: 10.3390/biom9070281
|View full text |Cite
|
Sign up to set email alerts
|

A Hydroxypropyl Methylcellulose-Based Solid Dispersion of Curcumin with Enhanced Bioavailability and Its Hepatoprotective Activity

Abstract: Curcumin is a polyphenol compound derived from the rhizomes of Curcuma longa that exhibits antioxidant, anti-inflammatory, anticancer, and antimicrobial properties. However, its low solubility in aqueous solutions, low absorption following oral administration, and rapid degradation limit its use as a functional food material. In this study, a hydroxypropyl methylcellulose-based solid dispersion of curcumin (DW-CUR 20) was prepared and its bioavailability was evaluated. In addition, its therapeutic efficacy as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…SDs of CM prepared using HPMC as the polymer have been reported by Shin et al [ 48 ], who studied their possible hepatoprotective action in HepG2 cells treated with tert-butyl hydroperoxide (t-BHP) as a hepatotoxic agent. The survival rate of cells, which in the presence of t-BHP was about 40%, significantly increased after treatment with DSs-CM at concentrations of 10, 20 and 40 µg/mL compared to the treatment with CM alone at equivalent concentrations (2, 4 and 8 µg/mL, respectively).…”
Section: In Vitro Study Of Solid Dispersions In Polymeric Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…SDs of CM prepared using HPMC as the polymer have been reported by Shin et al [ 48 ], who studied their possible hepatoprotective action in HepG2 cells treated with tert-butyl hydroperoxide (t-BHP) as a hepatotoxic agent. The survival rate of cells, which in the presence of t-BHP was about 40%, significantly increased after treatment with DSs-CM at concentrations of 10, 20 and 40 µg/mL compared to the treatment with CM alone at equivalent concentrations (2, 4 and 8 µg/mL, respectively).…”
Section: In Vitro Study Of Solid Dispersions In Polymeric Matricesmentioning
confidence: 99%
“…Instead, Shin et al [ 48 ] tested in vivo the hepatoprotective activity of CM-containing SDs with HPMC against tert-butyl hydroperoxide (t-BHP)-treated mice by administering 80 mg/kg of CM (positive control) or an equivalent dose of SD (400 mg/kg). Levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), which indicate liver damage in response to t-BHP, were reduced by SD, while CM alone had no statistically significant effect.…”
Section: In Vivo Studies On Solid Dispersions In Polymeric Matricementioning
confidence: 99%
“…The FESEM images are shown in Figure 3, exhibiting clearly the dispersion state of pure IMC and SDs. The shape of pure drug particles is observed in Figure 3A, and the pure IMC was regarded as a "crystalline form" because of its natural crystalline state with a particle size varying from 20 to 100 µm [22]. The SEM image of pure IMC showed a slightly smooth surface and plate-shaped particles ( Figure 3A), whereas that of F3 ( Figure 3B), F6 ( Figure 3C), and F9 ( Figure 3D) showed spherical-shaped, smooth-surfaced SDs.…”
Section: Field Emission Scanning Electron Microscopy (Fesem)mentioning
confidence: 99%
“…Different measurements can obtain various values of PAMPA permeability coefficients, just like the so-called percentage of flux (%F) or transported solute (%T) which measures the part of the test compound in the acceptor compartment. The PAMPA is able to rapidly determine the tendency of compounds to penetrate membranes by passive diffusion and is therefore suitable for screening solid dispersion and relative drugs [22].…”
Section: Permeability and Bioavailability Studiesmentioning
confidence: 99%
“…Cellulose in association with collagen was used for the fabrication of nanocrystals composite scaffolds containing curcumin-loaded gelatin microspheres (Cur/GMs/Coll-CNCs) [34]. This approach was employed due to the low stability and high hydrophobicity of curcumin, a compound highlighted for high therapeutic potential as antimicrobial, healing, and anti-inflammatory agent [84][85][86][87]. The authors showed that curcumin was released in a controlled and sustained way from the scaffolds.…”
Section: Cellulose-based Formulationsmentioning
confidence: 99%